Mechanical characterization and fractography of glass fiber/polyamide (PA6) composites. Issue 5 (11th April 2014) - Durai Prabhakaran, R.T.; Pillai, Saju; Charca, Samuel; Oshkovr, Simin A.; Knudsen, Hans; Andersen, Tom Løgstrup; Ilsted Bech, Jakob; Thomsen, Ole Thybo; Lilholt, Hans
<x xml:space="preserve">Abstract</x> The mechanical properties of the glass fiber reinforced Polyamide (PA6) composites made by prepreg tapes and commingled yarns were studied by in‐plane compression, short‐beam shear, and flexural tests. The composites were fabricated with different fiber volume contents (prepregs—47%, 55%, 60%, and commingled—48%, 48%, 49%, respectively) by using vacuum consolidation technique. To evaluate laminate quality in terms of fiber wet‐out at filament level, homogeneity of fiber/matrix distribution, and matrix/fiber bonding standard microscopic methods like optical microscopy and scanning electron microscopy (SEM) were used. Both commingled and prepreg glass fiber/PA6 composites (with Vf ∼ 48%) give mechanical properties such as compression strength (530–570 MPa), inter‐laminar shear strength (70–80 MPa), and transverse strength (80–90 MPa). By increasing small percentage in the fiber content show significant rise in compression strength, slight decrease in the ILSS and transverse strengths, whereas semipreg give very poor properties with the slight increase in fiber content. Overall comparison of mechanical properties indicates commingled glass fiber/PA6 composite shows much better performance compared with prepregs due to uniform distribution of fiber and matrix, better melt‐impregnation while processing, perfect alignment of glass fibers in the composite. This study proves again that the presence of voids and poor interface bonding between matrix/fiber leads to decrease in the mechanical properties. Fractographic characterization of post‐failure surfaces reveals information about the cause and sequence of failure. POLYM. COMPOS., 36:834–853, 2015. © 2014 Society of Plastics Engineers